Lithium-induced gene expression alterations in two peripheral cell models of bipolar disorder. (3rd July 2019) - Kittel-Schneider, Sarah; Hilscher, Max; Scholz, Claus-Jürgen; Weber, Heike; Grünewald, Lena; Schwarz, Ricarda; Chiocchetti, Andreas G.; Reif, Andreas
Abstract: Objectives: The aim of our study was to investigate molecular mechanisms of lithium action by studying the gene expression profile of peripheral cell models generated from bipolar patients (BD) and healthy controls (HC). Methods: EBV-immortalised lymphoblastoid cells (LCLs) and fibroblast cells from BD and HC were incubated with either lithium chloride or plain medium for 3 weeks. We first conducted a microarray gene expression study. The most promising differentially regulated genes in terms of lithium-associated or disorder-associated pathways were then replicated by quantitative real-time PCR (qRT-PCR). Results: The pooled microarray analysis showed 459 genes to be differentially regulated in BD compared to HC and 58 due to lithium treatment in LCLs, and 295 genes to be differentially regulated in BD compared to HC and five due to lithium treatment in fibroblasts. After correction for multiple comparison, EPHB1 disorder × treatment interactions remained significant in LCLs validated by qRT-PCR. In the control group, lithium influenced the expression of ANP32E, PLEKHA2, KCNK1, PRKCH, ST3GAL6 and AIF1 . In bipolar and control fibroblast cells lithium treatment decreased FGF9 expression. Conclusions: The differentially regulated genes in our study add evidence for the relevance of inflammation, neuronal/glial development, phosphatidylinositol second-messenger pathway and ion channels in the mode of action of lithium.